Muyong et subak. Production agricole, patrimoine culturel et enjeux environnementaux dans les rizières en terrasses de Bali (Indonésie) et du pays Ifugao de Luçon (Philippines) - Yves Boquet (Bulletin de l’Association de Géographes Français)
The terraced rice fields of Bali and the northern Philippines are not just spectacular agricultural production sites located in hilly or mountainous areas. Their development by the Hindu Balinese and the non-Christianized Ifugao includes a strong religious dimension as well as a complex social organization around the management of water resources. The recent rise of tourism, coupled with the UNESCO world heritage recognition of these agricultural areas, leads today to several challenges that may jeopardize the balance of these societies: tourism overcrowding, loss of authenticity, abandonment of farming by young people. Are these sophisticated local farming systems sustainable in the context of globalization? Which arrangements can insure their survival?